Risk of malignancy following exposure to Epstein-Barr Virus associated infectious mononucleosis: A nationwide population-based cohort study - Cai, Kang; Zhou, Baosong; Huang, Heyu; Tao, Rong; Sun, Jian; Yan, Chonghuai; Lee, Priscilla Ming Yi; Svendsen, Katrine; Fu, Bo; Li, Jiong; Huang, Lisu (Frontiers in Oncology, 2022)
Abstract Purpose Epstein-Barr virus (EBV) infection has been shown to contribute to oncogenesis and often causes acute clinical manifestation of Infectious mononucleosis (IM). The association of IM and subsequent malignancies remains unclear. We aimed to evaluate the association of IM with overall and subtypes of malignancy. Methods This population-based cohort study included 1,419,407 individuals born in Denmark between 1973 and 2016. Of those, 23,057 individuals with IM, including 5,394 with confirmed EBV-IM, were birth date- and sex- matched (1:63) to 1,396,350 non-IM individuals. Cox regression was used to examine the associations of EBV-IM with malignancy. Results Individuals with a history of confirmed EBV-IM had an 88% increased overall risk of malignancy (hazard ratio [HR]:1·88, 95% confidence interval [CI]: 1·42–2·49) and a five-fold risk of hematologic malignancies (HR 5·04, 95% CI: 3·07–8·25), compared to those without IM. Similar estimates were observed in the sibling analysis. The overall risk of malignancy was greater for EBV-IM with complications (HR 8·93, 95% CI: 3·35–23·81) than of that without complications (HR 1·35, 95% CI: 1·20–1·53). EBV-IM duration was related to increased risk of malignancy in a dose-response way. Notably, the significant elevated risk of overall malignancy was observed in the first two years after EBV-IM onset (rate ratio [RR] 4·44, 95% CI: 2·75–7·17) and attenuated thereafter. Conclusion EBV-IM was associated with an increased risk in malignancy, particularly hematologic malignancies and in the first two years following IM exposure. Our findings suggest an important time-window for early screening of the EBV-attributed malignancy.